Effects of ATPM-ET, a novel κ agonist with partial μ activity, on physical dependence and behavior sensitization in mice - Sun Jian-feng; Wang Yu-hua; Li Fu-ying; Lu Gang; Tao Yi-min; Cheng Yun; Chen Jie; Xu Xue-jun; Chi Zhi-qiang; Neumeyer John L; Zhang Ao; Liu Jing-gen (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of ATPM-ET [(−)-3-N-Ethylaminothiazolo [5,4-b]-N-cyclopropylmethylmorphinan hydrochloride] on physical dependence and behavioral sensitization to morphine in mice. Methods: The pharmacological profile of ATPM-ET was characterized using competitive binding and GTPγS binding assays. We then examined the antinociceptive effects of ATPM-ET in the hot plate test. Morphine dependence assay and behavioral sensitization assay were used to determine the effect of ATPM-ET on physical dependence and behavior sensitization to morphine in mice. Results: The binding assay indicated that ATPM-ET ATPM-ET exhibited a high affinity to both κ- and μ-opioid receptors with Ki values of 0.15 nmol/L and 4.7 nmol/L, respectively, indicating it was a full κ-opioid receptor agonist and a partial μ-opioid receptor agonist. In the hot plate test, ATPM-ET produced a dose-dependent antinociceptive effect, with an ED50 value of 2.68 (2.34–3.07) mg/kg. Administration of ATPM-ET (1 and 2 mg/kg, sc) prior to naloxone (3.0 mg/kg, sc) injection significantly inhibited withdrawal jumping of mice. In addition, ATPM-ET (1 and 2 mg/kg, sc) also showed a trend toward decreasing morphine withdrawal-induced weight loss. ATPM-ET (1.5 and 3 mg/kg, sc) 15 min before the morphine challenge significantly inhibited the morphine-induced behavior sensitization (P